The Influence of Digital Marketing and Brand Awareness on Increasing Walini Tea Sales - Octariviani, Veny (Riwayat: Educational Journal of History and Humanities, 2025)
Tea is one of the most widely consumed beverages in Indonesia. Tea drinks are favored by various groups and ages as an everyday drink that is easy to find and make. Tea (Camellia sinensis) is a commodity that is a mainstay of the plantation sector in Indonesia. One of the tea brands managed by PT Perkebunan Nusantara I Regional 2 is Teh Walini. Teh Walini is a tea that has advantages over other brands, has high quality because it comes from its own plantation and goes through a modern processing process to produce an authentic taste and has various flavor variants. In its marketing activities, Teh Walini utilizes digital marketing, especially through social media, to introduce its products by expanding its market reach. The objectives to be achieved in this study are to find out the characteristics of Teh Walini consumers and analyze how digital marketing (Y1) and brand awareness (Y2) affect Sales Increase (X). The study was conducted using a sampling method on 42 (forty-two) buyers of Teh Walini. The data were analyzed using a simple linear regression analysis model and a multiple linear regression analysis model. Using SPSS software version 25. The results of the study show that there is an influence of digital marketing on product sales, there is an influence of brand awareness on product sales, and there is a joint influence of digital marketing and brand awareness on product sales.